2004
DOI: 10.1080/00016470410001231
|View full text |Cite
|
Sign up to set email alerts
|

Neck fracture femoral heads for impaction bone graftingEvolution of stiffness and compactness during impaction of osteo-arthrotic and neck-fracture femoral heads

Abstract: Solvent-treated freeze-dried bone from femoral heads procured during arthroplasty for sub-capital hip fractures represents a valuable source of material for allografts, addressing concerns regarding serological testing, medical history and bone quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…PVCR, as an alternative strategy for vertebral column resection, requires a posterior bilateral approach and has a shorter operation time and reduced blood loss as compared with the traditional vertebral column resection. 13 15 Yang et al 6 demonstrated that as the first operative approach, the overall prevalence of PVCR complications was 32%, with the most common being neurological complications (8%). Chen and Dai 4 reported a 40% complication rate with PVCR as a revision strategy, which is similar to the above rate for PVCR as revision surgery (36.7%), but significantly higher than that of PUVCR complications (7.1%).…”
Section: Discussionmentioning
confidence: 99%
“…PVCR, as an alternative strategy for vertebral column resection, requires a posterior bilateral approach and has a shorter operation time and reduced blood loss as compared with the traditional vertebral column resection. 13 15 Yang et al 6 demonstrated that as the first operative approach, the overall prevalence of PVCR complications was 32%, with the most common being neurological complications (8%). Chen and Dai 4 reported a 40% complication rate with PVCR as a revision strategy, which is similar to the above rate for PVCR as revision surgery (36.7%), but significantly higher than that of PUVCR complications (7.1%).…”
Section: Discussionmentioning
confidence: 99%
“…They describe an average 38 degrees of correction in the sagittal plane without any neurological injury or pseudoarthrosis during a 2-year follow-up period after BDBO, with a range between 35 and 60 degrees based on type of BDBO performed. [ 2 3 4 ] The technique described in our report can be seen as a modified type I BDBO, where the disk space is not removed. Similar to our claim, Enercan et al .…”
Section: Discussionmentioning
confidence: 99%
“…How can a softer material give a stiffer reconstruction? In our experiments, freeze-dried irradiated bone appeared to get impacted faster than the frozen control whatever the particle size (81)(82)(83). During an impaction bone grafting procedure, the stress is applied at such high speed that the flow of liquids may play an important role (84) and the replacement of bone marrow by saline in the processed bone may accelerate the grafts compaction (85).…”
Section: Embrittlement Theorymentioning
confidence: 92%